Pengenalan KeAl-Washliyahan sebagai Penguatan Akhlak Anak Usia Dini di RA Al-Washliyah Kisaran - Rahman, Mhd Habibu (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Al-Washliyah is an Islamic mass organization that pays great attention to the world of education. The Al-Washliyah educational institution prioritizes spiritual values in the implementation of learning so that it is able to answer the community's need for the importance of religious education and strengthening morals. The aim of this research is to find out the process of introducing Al-Washliyah to early childhood carried out by teachers and how the introduction of Al-Washliyah is related to strengthening children's morals at RA Al-Washliyah Kisaran. The method used in this research is qualitative with data collection techniques using participant observation and in-depth interviews. All existing data is analyzed using the stages of data condensation, data display and verification. The research results stated that the process of introducing Al-Washliyahan to early childhood at RA Al-Washliyah was delivered by maximizing the quality of educators in delivering Al-Washliyahan material in an interesting and enjoyable form of learning. As for the activities carried out, such as prayer programs, remembrance and prayer memorization, Al-washliyahan material is integrated with developmental aspects that can strengthen children's morals. Simple and fun forms of activities can strengthen children's morals.